Joseph G. Clark papers - Clark, Joseph G.
Journal (1838 August-1841 May) kept by Clark during the Wilkes Expedition (United States Exploring Expedition). Describes many details of the voyage on the flagship Vincennes.
Sailor.
Collection material in English.
Keywords: Wilkes, Charles, -- 1798-1877.; Vincennes (Sloop of war); Sailors